Evaluating the Sustainability of Local Women's Climate Change Adaptation Strategies in Durban, South Africa: A Feminist Political Ecology and Intersectionality Perspective - Fidelis Udo; Johannes Bhanye; Balkissa Daouda Diallo; Maheshvari Naidu (Sustainable Development, 2024)
This paper employs a feminist political ecology and an intersectionality framework to examine the multiple dimensions of local women's vulnerability and adaptation to climate change impacts in selected locations in Durban, KwaZulu-Natal Province, South Africa. We focus particularly on assessing the sustainability of the gendered adaptive strategies employed by these women. Utilising a qualitative methodology, the study is based on semi-structured interviews and focus group discussions with local Black women, highlighting the local context of the women's adaptation to flood impacts. The findings revealed that adaptation strategies are informed by women's situated knowledge, cultural practices, and agency, illustrating the complex, context-specific nature of responses to climate challenges. We argue that a bottom-up approach, which prioritises the effectiveness and sustainability of women's adaptation strategies, is crucial for fostering longer-term, more equitable, and sustainable solutions to climate impacts. By advocating this approach, the paper contributes to a deeper understanding of gendered adaptation practices that align with global efforts to achieve the Sustainable Development Goals (SDGs) related to gender equality (SDG 5), reducing inequalities (SDG 10), promoting climate action (SDG 13), and sustainable cities and communities (SDG 11).
Keywords: 330; Durban; feminist political ecology; gender and climate change adaptation; intersectionality; local black women; South Africa; sustainability